An economic analysis of immediate delivery and expectant monitoring in women with hypertensive disorders of pregnancy, between 34 and 37 weeks of gestation (HYPITAT‐II). (10th March 2016) - van Baaren, G‐J; Broekhuijsen, K; van Pampus, MG; Ganzevoort, W; Sikkema, JM; Woiski, MD; Oudijk, MA; Bloemenkamp, KWM; Scheepers, HCJ; Bremer, HA; Rijnders, RJP; van Loon, AJ; et al.
Abstract : Objective: To assess the economic consequences of immediate delivery compared with expectant monitoring in women with preterm non‐severe hypertensive disorders of pregnancy. Design: A cost‐effectiveness analysis alongside a randomised controlled trial (HYPITAT‐II). Setting: Obstetric departments of seven academic hospitals and 44 non‐academic hospitals in the Netherlands. Population: Women diagnosed with non‐severe hypertensive disorders of pregnancy between 34 0/7 and 37 0/7  weeks of gestation, randomly allocated to either immediate delivery or expectant monitoring. Methods: A trial‐based cost‐effectiveness analysis was performed from a healthcare perspective until final maternal and neonatal discharge. Main outcome measures: Health outcomes were expressed as the prevalence of respiratory distress syndrome, defined as the need for supplemental oxygen for >24 hours combined with radiographic findings typical for respiratory distress syndrome. Costs were estimated from a healthcare perspective until maternal and neonatal discharge. Results: The average costs of immediate delivery ( n  = 352) were €10 245 versus €9563 for expectant monitoring ( n  = 351), with an average difference of €682 (95% confidence interval, 95% CI −€618 to €2126). This 7% difference predominantly originated from the neonatal admissions, which were €5672 in the immediate delivery arm and €3929 in the expectant monitoring arm. Conclusion: In women with mild hypertensive disorders between 34 0/7 and 37 0/7  weeks of gestation, immediate delivery is more costly than expectant monitoring as a result of differences in neonatal admissions. These findings support expectant monitoring, as the clinical outcomes of the trial demonstrated that expectant monitoring reduced respiratory distress syndrome for a slightly increased risk of maternal complications. Tweetable abstract: Expectant management in preterm hypertensive disorders is less costly compared with immediate delivery. Abstract : Expectant management in preterm hypertensive disorders is less costly compared with immediate delivery.